GLOBAL CIVIL SOCIETY AND HUMANITARIAN CRISES: HOW WANEP PLAYS ITS ROLE IN WEST AFRICA IN 2019 - Abd Azis; Muhammad Fadilah Aziz; Mutiarah Azizah Dyah Pramesti; Herdiani Narita; Novita Putri Rudiany; Indra Kusumawardhana (Universitas Nasional, 2023)
Many reports in the mass media regarding the humanitarian crisis caused by economic and political instability in West Africa continued to become headlines that were widely discussed throughout 2019. The saying